Comparison of the cardiovascular effects of immobilization with three different drug combinations in free-ranging African lions. Issue 1 (12th January 2023) - Donaldson, Ashleigh Claire; Meyer, Leith Carl Rodney; Fuller, Andrea; Buss, Peter Erik
Abstract : Drug combinations used to immobilize lions work well to sedate them but have adverse effects on the way their heart functions. We compared two new drug combinations to the conventional combination and found that all caused high blood pressure, but one of the new combinations had fewer adverse effects overall. Abstract: Thirty-six free-ranging lions (12 per group) were immobilized with tiletamine–zolazepam (Zoletil 0.6 mg/kg i.m.) plus medetomidine (0.036 mg/kg i.m.) (TZM), ketamine (3.0 mg/kg i.m.) plus medetomidine (0.036 mg/kg i.m.) (KM) or ketamine (1.2 mg/kg i.m.) plus butorphanol (0.24 mg/kg i.m.) plus medetomidine (0.036 mg/kg i.m.) (KBM). During immobilization cardiovascular variables were monitored at 5-minute intervals for a period of 30 minutes. Lions immobilized with all three drug combinations were severely hypertensive. Systolic arterial pressure was higher at initial sampling in lions immobilized with KM (237.3 ± 24.8 mmHg) than in those immobilized with TZM (221.0 ± 18.1 mmHg) or KBM (226.0 ± 20.6 mmHg) and decreased to 205.8 ± 19.4, 197.7 ± 23.7 and 196.3 ± 17.7 mmHg, respectively. Heart rates were within normal ranges for healthy, awake lions and decreased throughout the immobilization regardless of drug combination used. Lions immobilized with TZM had a higher occurrence (66%) of skipped heart beats than those immobilized with KBM (25%). The three drug combinations all caused negative cardiovascular effects, which were less when KBM was used, but adverse enough to warrant further investigations to determine if these effects can be reversed or prevented when these three combinations are used to immobilize free-living lions.